Evaluation of online video content related to reverse shoulder arthroplasty: a YouTube-based study - Mohamad Y. Fares; Jonathan Koa; Peter Boufadel; Jaspal Singh; Amar S. Vadhera; Joseph A. Abboud (Clinics in Shoulder and Elbow, 2023)
Background Reverse shoulder arthroplasty (RSA) has evolved continuously over recent years, with expanded indications and better outcomes. YouTube is one of the most popular sources for health-related information available to patients. Evaluating the quality of YouTube videos concerning RSA is important to ensure proper patient education. Methods YouTube was queried for the term “reverse shoulder replacement.” The first 50 videos were evaluated using three different scores: Journal of the American Medical Association (JAMA) benchmark criteria, the global quality score (GQS), and the reverse shoulder arthroplasty-specific score (RSAS). Multivariate linear regression analyses were conducted to determine the presence of a relationship between video characteristics and quality scores. Results The average number of views was 64,645.78±264,160.9 per video, and the average number of likes was 414 per video. Mean JAMA, GQS, and RSAS scores were 2.32±0.64, 2.31±0.82, and 5.53±2.43, respectively. Academic centers uploaded the highest number of videos, and surgical techniques/approach videos was the most common video content. Videos with lecture content predicted higher JAMA scores whereas videos uploaded by industry predicted lower RSAS scores. Conclusions Despite its massive popularity, YouTube videos provide a low quality of information on RSA. Introducing a new editorial review process or developing a new platform for patients’ medical education may be necessary. Level of evidenceNot applicable.